Characterization of patients in the emergency services with acute pulmonary edema - Marlene Fong Ocejo; Gerardo Téllez Gamayo; Eddy Amaury Martínez Soler; Disnay Tamayo Blanco (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: Acute pulmonary edema is a frequent disease among patients in emergency services. Objective: To characterize patients with acute pulmonary edema who attended the emergency services. Methods: A descriptive and cross-sectional study of 37 patients with acute pulmonary edema who attended the emergency services of Dr. Joaquín Castillo Duany Teaching Clinical Surgical Hospital in Santiago de Cuba was carried out, from January to November 2019. The studied variables were age, sex, alive or dead when discharged, noninvasive ventilation usage. Results: There were no differences between the sexes; there was a prevalence of patients older than 60 years of age, who suffered from hypertension. It was demonstrated low noninvasive or invasive ventilation usage. Conclusions: Acute pulmonary edema is more frequent among patients older than 60 years of age in both sexes. Most of the patients suffered from hypertension and there was a deficit in the implementation of noninvasive ventilation in these cases.